DEVELOPMENT OF A PROACTIVE PSYCHOSOCIAL THERAPY PROGRAM FOR THE KAO WAN MAI CLINIC FOR TREATING DRUG ADDICTS IN NADEE DISTRICT, PRACHINBURI PROVINCE - Konsanthad, Tutiyaporn (Journal of MCU Nakhondhat, 2025)
This research and development aimed to 1) Study the current issues in drug addiction treatment and identify the essential needs for developing a proactive psychosocial therapy program, 2) Develop a proactive psychosocial therapy program, and 3) Evaluate the effectiveness of the proactive psychosocial therapy program at the Kao Wan Mai Clinic, Nadi Hospital, Prachinburi Province. This study utilizes a research and development approach, utilizing a mixed-methods research methodology. The key informants comprised 9 individuals, including hospital administrators, nurses at the Kao Wan Mai Clinic, patients undergoing treatment, related personnel, and staff from agencies involved in drug prevention and control. The sample also included 323 residents of Nadi District who received services at Nadi Hospital, Prachinburi. Experts involved include 10 individuals from Nadi Hospital’s administration, personnel from the Ministry of Public Health, community leaders, and police officers, along with 30 patients receiving drug addiction treatment. Qualitative data was analyzed using content analysis, and quantitative data was analyzed through frequency, percentage, mean, and standard deviation. Need assessment was conducted using the PNI index, and hypotheses were tested by comparing means to predefined criteria. The results showed: 1) Drug addiction treatment faces challenges in communication and participation. Key needs for development include enhancing communication effectiveness and fostering participation. 2) The proactive psychosocial therapy program consists of six steps rated highly suitable, feasible, beneficial, and accurate. and 3) The overall well-being of patients receiving treatment was high (µ = 4.28, S.D. = .490). Hypothesis testing results indicate that patients undergoing addiction treatment have a high level of well-being.